Comparative Analysis of Environmental Graphic Design for Wayfinding on the Exit Patterns of Mass Transit Stations - Pakachart Puttipakorn; Prapatpong Upala (My University, 2018)
Introduction: The quality of transit services has long been recognized as a significant factor affecting passenger behavior and station quality. The objective of this paper was to compare the environmental graphic designs for passengers’ decision to choose walking ways in subway stations of Bangkok Metropolis, Thailand. Methods: It uses the multi-stage sampling approach at various forms of station entries-exits and traffic statistics of service usage by passengers. The forms of station entries-exits can be divided into four types: 1) Silom Station (2-way exits), 2) Sukhumvit Station (3-way exits), 3) Huai Khwang Station (4-way exits), and 4) Phahon Yothin Station (5-way exits). Questionnaires were used to collect data from 445 passengers, using Likert Scale and t-test/ANOVA. The comparative analysis of directional signs was conducted with three factors as follows; 1) signs with 1-point location, 2) signs with 2-point locations, and 3) signs with 3-point locations. Results: The results found the signs with 2-point locations could provide additional information about the places and were suitable for the general environment of all stations. However, when adding further information about the places on the signs with 3-point locations, some limitations were found regarding the passengers’ need for location information with a complex physical environment of the station. Also, when considering the passengers’ attributes and behaviors, it was found that they also affected the environmental graphic design significantly. Conclusion: The research findings can be used as information for the environmental graphic designers to develop wayfinding system to improve for passengers’ travelling in mass transit stations.
Keywords: Subway station; Spatial Cognition and Navigation